TAHRIR CINEMA Film Activism in Egypt's Revolution. - Howe, Esther (Glimpse: The Art & Science of Seeing)
The article focuses on the Mosireen, a non-profit media center founded by a group of artists and activists in Downtown Cairo, Egypt in April 2011. It states that the organization aims to empower the citizen's perspective and provide space and technical support for mass media production. Also mentioned are the emerging issues in the country which include corruption, inconsistent Internet access, and state-run media.